Web Accessibility in the Field of Social Services and Benefits in Romania - Marin, Anca Monica; Popa, Liliana (Calitatea Vieții, 2024)
This paper examines the current situation in Romania in terms of web accessibility provided by two key institutions in the field of administering social services and benefits in Romania – County Directorates of Social Work and Child Protection (DGASPC) as well as County Pensions Houses (CJP). As the pandemic context further accelerated the development of e-government worldwide, there is a strong need to ensure information and communication accessibility for persons with disabilities and persons with functional limitations in general. The assessment grid is represented by the Web Content Accessibility Guidelines (WCAG) 2.1 requirements and techniques, mainly regarding Level A, minimum level of conformance. Results underline significant discrepancies in implementing various accessibility characteristics among similar institutional bodies and the needs to take further steps to improve accessibility. The study adds knowledge on the larger topic of digital inclusion, as a contributor to enhanced social inclusion. It also contributes to the international debate on web accessibility evaluation and developing accessibility in web design, especially in the case of public authorities who have under their responsibility services directly addressed to persons with disabilities or to older persons with visual or hearing impairments.